How the Agri-Food Supply Chain Impacts Poverty in Rural Areas: Case Study in Norway - Håkon Kristine Harald (GoAcademica Research & Publishing, 2023)
The great agri-food supply chain has had a decisive influence on the recent worsening of the agricultural crisis traditionally suffered by country farming, not only in underdeveloped countries but also in the developed world. Due to their increasing global power and territorial and economic growth, suppliers now have total control of the whole food chain. Consequently, they select only those producers who are able to comply with the strict rules and regulations enforced as regards product quality, quantity and appearance, forging close links with the agro industry and agro-export models. The agri-food chain in Norway is a complex and dynamic sector that faces a range of challenges related to sustainability, equity, and globalization. To address these challenges, it will be important to engage in interdisciplinary and participatory research that involves stakeholders from across the sector.